ORGANIZING PRACTICAL CHEMISTRY LESSONS AT SCHOOL USING INFORMATION COMMUNICATION TECHNOLOGIES - Navrozbek Shermuhammadugli Amonov; Murad Makhmarajab ugli Jurayev (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the concepts and methods of teaching practical chemistry lessons using ICT and the observed effectiveness of these methods among students.